Aflatoxin Growth versus Safe Pre- and Post-Harvest Drying and Storage - Villers , Philippe (Journal of Postharvest Technology, 2015)
Discussed are field tested solutions including Ultra Hermetic storage™ contributing to solving the dual global issues of reducing food losses and protecting food safety during drying and storage of grains in a world of growing climate change.Data is provided on post harvest losses, on the public health hazard posed by aflatoxins, and how these problems are aggravated by hot, humid climates. Field data on drastically reducing growth of aflatoxins in storage is described. The storage requirements for moisture control and oxygen levels are specified for pesticide-free storage using airtight storage, including hermeticity requirements needed. Such systems are now used in 107 countries. Benefits include major storage loss reduction – typically to less than 1% for up to 1-year of storage even in the tropics, as compared to typical losses up to 25%, and the inhibition of growth of aflatoxin-producing molds. Data on the application of the same technology to safe, multi-month seed storage without refrigeration as documented by the IRRI and others. Quantitative data is presented. Comparison of conventional storage, air-conditioned and refrigerated storage with Ultra Hermetic storage is provided.Also described are the available forms of both Ultra Hermetic Storage and improved solar drying for cost effective solutions to improve both farmer income and nutrition during what many developing countries refer to as the “starving season”. This helps solve food insecurity with increased abilities to preserve commodities in good condition for up to a year or more, as well as facilitate exports by meeting international standards.